PENGARUH PANDEMIK COVID-19 TERHADAP KUALITAS UDARA DI BEBERAPA KOTA BESAR DI INDONESIA MEMANFAATKAN DATA PERMODELAN CUACA - Nugroho, Anendha Destantyo (Jurnal Widya Climago, 2020)
In the early 2020s, the world was shocked by the coronavirus outbreak (Covid-19) which infected almost alcountries in the world. As the rapid spreading of the virus and its impact on respiratory disorders and itcomplications with other diseases causes the world health organization or WHO declared Covid-19 to be apandemic on March 11. The policies in many countries imposed lockdown or social distancing to preventransmission of this virus which results in limited human activities. However, policies that are not concurrent ineach country and even cities caused the reduction of pollutants will vary. The purpose of this research is to findout the differences density of air pollutants in the atmosphere before and after the Covid-19 in big cities inIndonesia using weather modeling data with Particulate Matter (PM) parameters of less than 10 µm. The resultshowed that the most significant decreased pollutant intensity in the Special Capital Region of Jakarta, the Cityof Bandung, and the City of Semarang. However, the reduction of pollutant density was less significant in the City of Surabaya.